2005
DOI: 10.17660/actahortic.2005.697.63
|View full text |Cite
|
Sign up to set email alerts
|

Oxifertigation and Foliar Nutrient Contents of Closed Soilless Rose Crop

Abstract: Oxygen diffusion in soilless culture systems in Mediterranean climate conditions is often quite low, especially in summer. This fact is seldom taken into account even though it could lead to plant development constraints, as for instance scarce root development or certain nutrient uptake deficits. A study of a rose crop in a soilless recirculating system with oxifertigation and nightly oxygen supply has been carried out to determine whether there is a cause-effect relationship between the production and growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Bar-Yosef and Lieth (2013) in experiment with cut rose found that the accumulation rate of K was inhibited when DOC was 1.7 mg L -1 but was unaffected in 5 mg L -1 compared to 7.5 mg L -1 . In another experiment with cut roses, Carazo et al (2005) reported an increase in K + and Ca 2+ leaf content under oxyfertigation treatment, while significant difference was not found for N leaf content. Morard et al (2000) reported that N uptake was the least affected by oxygen deficiency.…”
Section: Discussionmentioning
confidence: 86%
“…Bar-Yosef and Lieth (2013) in experiment with cut rose found that the accumulation rate of K was inhibited when DOC was 1.7 mg L -1 but was unaffected in 5 mg L -1 compared to 7.5 mg L -1 . In another experiment with cut roses, Carazo et al (2005) reported an increase in K + and Ca 2+ leaf content under oxyfertigation treatment, while significant difference was not found for N leaf content. Morard et al (2000) reported that N uptake was the least affected by oxygen deficiency.…”
Section: Discussionmentioning
confidence: 86%